Plea decision-making: the influence of attorney expertise, trustworthiness, and recommendation - Henderson, Kelsey S. (Psychology, crime & law, 2020)
Attorney recommendations influence defendant plea decisions; and the degree of influence likely rests on the perceived trustworthiness and level of expertise of the attorney (factors of source credibility). We explored attorney source credibility factors and how these characteristics influence defendants’ plea decision-making. MTurk participants read a hypothetical plea scenario and were asked to imagine themselves as the defendant in a DWI/DUI case making a plea decision; in the scenario, we manipulated the defense attorney’s level of trustworthiness, expertise, and plea recommendation. There was a significant interaction between attorney recommendation and trustworthiness on defendants’ plea decisions; participants who were advised to accept the guilty plea were more likely to plead guilty when the attorney was high in trustworthiness compared to low in trustworthiness. Attorney trustworthiness did not affect plea decisions for defendants advised to reject the guilty plea. Importantly, attorney trustworthiness affected defendants’ decision to follow the attorney’s recommendation and ultimate plea decision (regardless of expertise), and attorney expertise affected defendants’ confidence in their decision (regardless of trustworthiness). Results suggest individual-level characteristics of defense attorneys affect the influence of the attorney and their recommendation, and ultimately defendants’ plea decision-making.